Analisis Implementasi Kebijakan Pembagian Kewenangan Pemerintah Provinsi dan Kabupaten/Kota dalam Pengelolaan Pelabuhan: Studi Kasus Pelabuhan Tengkayu I, Kota Tarakan - Patantan, Fredy; Milwan, Milwan; Abdullah, Sait (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
The implementation of regional governance policies in Indonesia has evolved through various legal frameworks, with the most recent being Law No. 23 of 2014. This law redefines the distribution of government authority, shifting certain responsibilities from district/city governments to provincial governments. One key sector affected by this change is port management, as seen in the case of Tengkayu I Port in Tarakan. The port's administration was transferred from the Tarakan City Government to the North Kalimantan Provincial Government to improve efficiency and service quality. However, this transition has faced challenges, particularly in maintaining service standards and public satisfaction. This study aims to analyze the implementation of the authority distribution policy at Tengkayu I Port, focusing on governance efficiency, policy execution, and its impact on service delivery. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The research applies Edwards III’s (1980) policy implementation framework, examining communication, resources, disposition, and bureaucratic structure as key factors influencing the success of the policy. The findings reveal that while regulatory frameworks and intergovernmental coordination facilitated the transition, challenges such as resource limitations, administrative adjustments, and declining public satisfaction need to be addressed. The study underscores the importance of structured policy implementation, regulatory clarity, and stakeholder engagement in ensuring effective governance transitions. Recommendations include enhancing capacity building at the provincial level and improving communication channels between stakeholders to optimize policy outcomes.